The millipede family Polydesmidae in Taiwan, with descriptions of five new species (Polydesmida, Diplopoda) - Sergei Golovatch; Elena V. Mikhaljova; Hsueh-Wen Chang (ZooKeys, 2011)
Polydesmidae are represented in Taiwan by seven species in two genera. Neither of the genera is endemic to Taiwan, but six of the species are, including five new: Nipponesmus minor sp. n., Epanerchodus bispinosus sp. n., E. curtigonopus sp. n., E. flagellifer sp. n. and E. pinguis sp. n. In addition, the diagnosis of the hitherto enigmatic genus Nipponesmus Chamberlin & Wang, 1953 is refined vis-à-vis the especially similar, Central Asian, Siberian and Eastern European genus Schizoturanius Verhoeff, 1931, chiefly based on new material of the type-species N. shirinensis Chamberlin & Wang, 1953; this species is adequately redescribed and represents still another Taiwanese endemic. A key to all three currently known species of Nipponesmus Chamberlin & Wang, 1953 is given. The highly speciose Central to East Asian genus Epanerchodus Attems, 1901 is represented in Taiwan by five species, all keyed, including E. orientalis Attems, 1901, which is long known to be highly variable in Japan and found particularly polymorphous and apparently allochthonous in Taiwan. The following synonymy is formalized: E. orientalis orientalis Attems, 1901 = E. orientalis takakuwai Verhoeff, 1913, syn. n. The genus Usbekodesmus Lohmander, 1932 is formally synonymized with Epanerchodus Attems, 1901, syn. n., resulting in the following new formal transfers: Epanerchodus redikorzevi (Lohmander, 1932), E. swatensis (Golovatch, 1991), E. varius (Geoffroy & Golovatch, 2004), E. anachoretus (Golovatch, 1986), E. buddhis (Golovatch, 1986), E. occultus (Golovatch, 1986), E. sacer (Golovatch, 1987), E. theocraticus (Golovatch, 1990) and E. theosophicus (Golovatch, 1986), all comb. n. ex Usbekodesmus. The distributions of all seven species of Polydesmidae occurring in Taiwan are mapped and discussed.